A selective colorimetric chemosensor for detection of Cu(II) ions in aqueous samples - Ferretti, Cristián Alejandro (2021)
In this work we report a selective colorimetric chemosensor (S) for Cu2+ ion detection in aqueous media. It has been synthesized by a condensation reaction between 1-hydrazinophtalazine and 6,60-dihydroxy-5,50dimethoxy-(1,10-biphenyl)-3,30-dicarbaldehyde. The interaction between S and Cu2+ was studied and the results showed a bathochromic shift at 420 nm in UV–Vis spectra. The absorbance enhancement of S was attributed to complex formation with Cu2+ by 2:1 stoichiometry. The proposed analytical method can be applied to Cu2+ quantification with a linear range covering from 5.0 to 315.8 µM, and can be used to routinely analyze Cu2+ in environmental aqueous samples with satisfactory results.